Nutrigenomics and nutraceuticals clinical relevance and disease prevention - Pathak, Yashwant (CRC Press, 2018)
Genomics and related areas of research have contributed greatly to the understanding of the cellular and molecular mechanisms underlying diet–disease relationships. In the past decade, the evidence has become stronger for a direct link between genome/epigenome damage and increased risk for adverse health outcomes. It is now exceedingly clear that micronutrients are critical as cofactors for many cellular functions, including DNA repair enzymes, methylation of CpG sequences, DNA oxidation, and/or uracil incorporation into DNA. Nutrigenomics and Nutraceuticals: Clinical Relevance and Disease Prevention brings new perspectives on disease prevention strategy based on the genomic knowledge and nutraceuticals of an individual and the diet he or she receives. This book discusses the integration and application of genetic and genomics technology into nutrition research and paves the way for the development of nutrition research programs that are aimed at the prevention and control of chronic disease through genomics-based nutritional interventions. In this book, the editors bring together a wide spectrum of nutritional scientists worldwide to contribute to the growing knowledge in the field of nutrigenomics and nutraceuticals.--Provided by publisher.